The Impact of Social Norms and Risk Assessment on Diners' Reaction to Food Safety Concerns in Restaurants. Issue 5 (2nd September 2020) - Harris, Kimberly; Depietro, Robin B.; Klein, Jesse; Jin, Dan
ABSTRACT: The purpose of this study was to investigate the behavioral reactions of diners when witnessing a food safety violation in a restaurant. Protection motivation and social norms theories were used to identify risk-related behavior to measure risk assessment, appraisal of food safety health threats, and the impact of descriptive and injunctive norms on reaction behaviors of diners in response to unsanitary food handler behavior and restaurant conditions. A mixed-methods approach was used with focus groups to develop the survey instrument that was distributed to 1, 800 recipients, resulting in 1, 169 usable surveys. Results suggest that if customers perceive a threat to be severe or if they have a belief that responding in a certain way will reduce the risk of a food safety concern, they are more apt to intervene to eliminate the threat. This study also shows that social norms mediate the influence of intervention, despite the severity of threat assessment. Practical and academic implications are discussed.